2017
DOI: 10.1111/sjos.12263
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of the Proportional Hazards Model with Time‐Varying Coefficients

Abstract: We study a Bayesian analysis of the proportional hazards model with time‐varying coefficients. We consider two priors for time‐varying coefficients – one based on B‐spline basis functions and the other based on Gamma processes – and we use a beta process prior for the baseline hazard functions. We show that the two priors provide optimal posterior convergence rates (up to the normallogn term) and that the Bayes factor is consistent for testing the assumption of the proportional hazards when the two priors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…In unreported numerical studies, we have found that these three choices lead to little practical difference in the properties of θ n (x) for x γ and n ≥ 1000. Kim et al (2017) proved that the rate of converge of the posterior distribution of the nonparametric Bayesian estimator proposed by Kim et al ( 2011) is (n/log n) −1/3 , which is the same as the pointwise rate of convergence of our estimator up to a log factor. However, to the best of our knowledge, it is not known whether the posterior distribution of the estimator proposed by Kim et al (2011) yields asymptotically calibrated confidence intervals for θ(x).…”
Section: Convergence In Distributionsupporting
confidence: 67%
“…In unreported numerical studies, we have found that these three choices lead to little practical difference in the properties of θ n (x) for x γ and n ≥ 1000. Kim et al (2017) proved that the rate of converge of the posterior distribution of the nonparametric Bayesian estimator proposed by Kim et al ( 2011) is (n/log n) −1/3 , which is the same as the pointwise rate of convergence of our estimator up to a log factor. However, to the best of our knowledge, it is not known whether the posterior distribution of the estimator proposed by Kim et al (2011) yields asymptotically calibrated confidence intervals for θ(x).…”
Section: Convergence In Distributionsupporting
confidence: 67%
“…Second, the proposed Bayesian inference for the PH model is developed based on the full likelihood with data augmentation. A valuable alternative is the partial likelihood‐based Bayesian inference procedure proposed by Kim et al, 40 which is asymptotically equivalent to the full likelihood‐based approach in terms of posterior convergence rate. Developing the partial likelihood approach in the context of the proposed model is worthy of investigation in the future.…”
Section: Discussionmentioning
confidence: 99%